The Sea Loan in Genoa in the Twelfth Century - Hoover, Calvin B. (Quarterly Journal of Economics, 1926)
Introductory: connection between the ancient Greek and Roman sea loan and the medieval Genoese type, 495. — Position of the sea loan before the Civil and Canon Law, 499. — The bona fide sea loan, 501. — Interest rates charged, 505. — Time and method of repayment, 507. — Security required, 508. — The pignus type of sea loan, 510. — Its importance as an addition to the credit machinery of Genoa, 511. — As a means of speculation, 518. — The usury-evasion type, 520. — Operation of the insurance principle, 523. — Relationship of medieval sea loan and modern bottomry bond, 526. — Conclusion, 528.